Development Of An Intelligent Controller For Solid State Fault Current Limiter - Nur Asyikin Binti Ghazali (2023)
There has been a growing focus on solving fault in distribution systems in recent years. Sensitive industrial loads and critical commercial operation all suffer from multiple kinds of power losses that can cost important losses per incident depending on process downtime, loss manufacturing, idle job forces and other variables. In order to resolve this issues, utility companies have made attempts to enhance the quality and reliability of their electrical power for customers. Currently, however, high-powered semiconductor devices such as door switch off thyristors and bipolar isolated gate transistors, various custom power devices have been designed to provide reliable alternatives to the issues of fault current in distribution networks. This thesis deals with the modelling and simulations of custom power devices, namely solid-state fault current limiter (SSFCL) with an intelligent controller of fuzzy logic controller (FLC). The modelling device for SSFCL of FLC is based on graphic models using simulation program SIMULINK/MATLAB. The use of the SSFCL was also developed to achieve quicker disruption and restriction of fault currents, respectively and with the help of FLC the system can optimize efficiently without any delay. Strategic SSFCL control approach for instant detection of overcurrent has been suggested. The SSFCL of FLC simulation findings indicate that it is an appropriate tool to reduce the fault current to the system's tolerable limit.